The historic tradition of wedding night-virginity test among Sri Lankan muslim women - Abdul Wadood, Noor Naleefa; Mimi Hanida Abdul Mutalib,; Yew, Wong Chin (Penerbit Universiti Kebangsaan Malaysia, 2023)
Studies all around the world confirm that virginity tests are conducted to find out a girl’s chastity and are celebrated in wedding ceremonies as a ritual among Sri Lankan Muslim women. This study attempts to provide a thriving understanding of the impacts of traumatic experiences related to the virginity test on Sri Lankan Muslim women's wedding nights. This study is a qualitative study with phenomenological aspects. Due to the sensitivity and hardness of selecting cases, the snowball sampling method was used. Accordingly, the current study was conducted in selected communities among Sri Lankan Muslims, and cases were selected from married Muslim women. Hence, nine cases were able to be studied in depth as case narratives; a focus group discussion and key informants were used to collect data. Study findings reveal that family members and relatives play an active role in the culture of testing virginity. It is perceived that the absence of blood stains has led to discomforts, doubts, misunderstandings, trauma, and violence in women’s lives. The study concludes that passive behavior, lack of proper sexual education, and shame and doubt related to sexuality have led Muslim women to face misery in their lives.